Room Temperature Synthesis and Catalytic Properties of Surfactant-Modified Ag Nanoparticles. (2nd October 2011) - Li, Weihua; Sun, Congtao; Hou, Baorong; Zhou, Xiaodong
Abstract : Well-dispersed Ag nanoparticles with size of 20–30 nm were synthesized in water at room temperature with a self-made novel imidazoline Gemini surfactant quaternary ammonium salt of di (2-heptadecyl-1-formyl aminoethyl imidazoline) hexanediamine. Transmission electron microscopy, X-ray powder diffraction, ultraviolet-visible absorption spectra, and Fourier transform infrared ray were used to characterize the Ag nanoparticles. Results showed that the micellized aggregation of imidazoline Gemini surfactant in water, the growth of Ag initial particles, and the interaction (adsorption and coordination) between surfactant and Ag + /Ag nanoparticles took place simultaneously to form the well-dispersed Ag nanoparticles. Catalytic results show that the surface-modified Ag product was an active metal catalyst for methyl orange reduction reaction due to the effective adsorption between Ag nanoparticles and methyl orange molecules, which was of promising application in environmental protection.